Perlindungan Lingkungan Dalam Perspektif Umar Bin Khattab - Dewi Risyantika; Ahmad Habibi; Muhammad Iqbal Fasa (Advances In Education Journal, 2025)
Environmental damage is one of the biggest problems facing modern humans, which is largely triggered by human behavior in excessive use of natural resources. In the tradition of Islamic thought, environmental fiqh (fiqh al-bi'ah) offers a normative approach that integrates the values ​​of faith, morals, and sharia in preserving nature. This article analyzes the ecological policies and thoughts of Umar bin Khattab (RA) as one of the important figures in Islamic history who applied the principles of environmental protection through economic, social, and public governance policies. This study uses a library research method with a qualitative approach and content analysis of various primary and secondary sources related to Umar R.A.'s policies. The results show that Umar placed the environment as a divine mandate, so that economic policies, land management, production, distribution, and consumption were directed towards maintaining the welfare and preventing damage (mafsadah). Umar in realizing protection and combating environmental abuse by carrying out basic warnings, maintaining a balance between the goals of economic growth and the goals of protecting the environment, protecting natural resources, combating pollution and maintaining the balance of the ecosystem. Umar's thoughts have been shown to reflect modern sustainability principles, such as intergenerational justice, resource conservation, ecosystem balance, and environmental health as prerequisites for economic growth. Therefore, environmental fiqh from Umar ibn Khattab's perspective can serve as an important reference in developing a holistic and applicable Islamic ecological framework for contemporary environmental issues.